2023
DOI: 10.2196/44822
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Trends and Underlying Factors of COVID-19 Vaccine Booster Hesitancy in Adults: Cross-Sectional Observational Study

Jian Wu,
Mingze Ma,
Quanman Li
et al.

Abstract: Background COVID-19 vaccine hesitancy reduces vaccination rates, which is detrimental to building herd immunity and halting the spread of COVID-19 and its variations. Most researches have simply identified the reasons affecting COVID-19 vaccination reluctance without delving into its dynamics, which makes forecasting future trends difficult. Objective This study aimed to examine the current COVID-19 vaccine booster hesitancy rate in Chinese adults as we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…In both the baseline and follow-up surveys, after adjustment for potential confounding variables, we found that participants with higher levels of education, chronic disease, a history of allergies, and lower levels of trust in medical staff and vaccine developers were more likely to be VH. Previous studies have found that people with higher levels of education instead exhibit higher VH ( Lazarus et al, 2022 ; Wu, Ma, et al, 2023 ). This may be because people with higher levels of education tend to have higher health literacy and healthier lifestyles, so that they do not consider further vaccination.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In both the baseline and follow-up surveys, after adjustment for potential confounding variables, we found that participants with higher levels of education, chronic disease, a history of allergies, and lower levels of trust in medical staff and vaccine developers were more likely to be VH. Previous studies have found that people with higher levels of education instead exhibit higher VH ( Lazarus et al, 2022 ; Wu, Ma, et al, 2023 ). This may be because people with higher levels of education tend to have higher health literacy and healthier lifestyles, so that they do not consider further vaccination.…”
Section: Discussionmentioning
confidence: 95%
“…This may be because people with higher levels of education tend to have higher health literacy and healthier lifestyles, so that they do not consider further vaccination. Another possible reason is that the well-educated population has more medical resources to protect themselves against the risk of disease ( Wu, Ma, et al, 2023 ). People with chronic diseases (hypertension, diabetes, etc.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that regular vaccination with booster shots can also lead to an increase in vaccine hesitation. 36 This study mainly discussed the effect of vaccine booster on vaccine hesitation,our future research may further explore the effect of the number of vaccine booster doses about vaccine hesitation and other possible influencing factors.…”
Section: Discussionmentioning
confidence: 98%
“…More details on the research design, survey process, and sample size selection is published elsewhere. 15,30 The public was not involved in setting the research question, the outcome measures, or the design or implementation of the study. In addition, all participants were invited to complete the digital informed consent and questionnaires.…”
mentioning
confidence: 99%